Impact of irrigation methods and mulching on vegetative growth, yield and quality of strawberry under mid hill conditions - SHARMA, VIKAS; KUMAR, RAJESH; TANDON, VIKAS; BHAT, ANIL (Journal of Soil and Water Conservation, 2020)
An experimental trial was conducted at Regional Agricultural Research Station, Rajouri during 2012- 2013 and 2013-2014 to determine the effects of irrigation methods and mulching material on growth, yield and quality of strawberry cultivar Chandler under mid hill conditions of Jammu province. Treatments comprised of two irrigation schedules (drip and flood irrigation) and three mulches viz. black polythene, paddy straw, chirpine needles and unmulched conditions. Results of the investigation revealed that strawberry is very responsive to the different irrigation methods and mulching materials. All the treatments improved the vegetative growth, yield and quality of strawberry, but treatment T1 (Drip Irrigation + black Polythene) which was closely followed by treatment T2 (Drip Irrigation + Transparent Polythene), which showed superiority in respect of growth, yield and quality parameters viz., plant height (18.11cm), plant spread (28.50 cm), petiole length (14.88 cm), leaf per plant (13.70), leaf area per plant (98.11 cm2), crown diameter (6.32 cm), crown weight (0.64 g), fruit yield per plant (332.92 g), fruit weight (32.08 g) fruit length (1.31 cm), fruit diameter (1.26 cm) specific gravity (1.17) and juice content (92.67%), which was closely followed over organic mulches and flood irrigation over unmulched + flood irrigation.